Therapeutic Communication on Satisfaction Through Health Motivation in Outpatient Patients of RSUD dr. M. Haulussy Ambon - Sinaga, Daniel; Zacharias, Tehubijuluw; Luhulima, Richard B. (Syntax Literate, 2025)
This study aims to analyze the effect of therapeutic communication on satisfaction through motivation to heal in outpatient installation patients of RSUD dr. M. Haulussy Ambon. The research approach used is quantitative with an associative explanation level through survey data collection with cross-section data types with the ex post facto method. The population used in this study were all patients in the outpatient installation of RSUD dr. M. Haulussy Ambon during June-August 2024. The sample determination was purposive as many as 100 outpatients of RSUD dr. M. Haulussy Ambon. Data were analyzed using path analysis. The results showed that when therapeutic communication is combined with high motivation to heal, the impact on patient satisfaction is significant. Patients with strong motivation are more eager to engage in the healing process and value interactions that support their health goals.